Compulsory admissions of patients with mental disorders: State of the art on ethical and legislative aspects in 40 European countries. Issue 1 (2020) - Wasserman, D.; Apter, G.; Baeken, C.; Bailey, S.; Balazs, J.; Bec, C.; Bienkowski, P.; Bobes, J.; Ortiz, M. F. Bravo; Brunn, H.; Bôke, Ö.; Camilleri, N.; et al.
Abstract: Background: Compulsory admission procedures of patients with mental disorders vary between countries in Europe. The Ethics Committee of the European Psychiatric Association (EPA) launched a survey on involuntary admission procedures of patients with mental disorders in 40 countries to gather information from all National Psychiatric Associations that are members of the EPA to develop recommendations for improving involuntary admission processes and promote voluntary care. Methods: The survey focused on legislation of involuntary admissions and key actors involved in the admission procedure as well as most common reasons for involuntary admissions. Results: We analyzed the survey categorical data in themes, which highlight that both medical and legal actors are involved in involuntary admission procedures. Conclusions: We conclude that legal reasons for compulsory admission should be reworded in order to remove stigmatization of the patient, that raising awareness about involuntary admission procedures and patient rights with both patients and family advocacy groups is paramount, that communication about procedures should be widely available in lay-language for the general population, and that training sessions and guidance should be available for legal and medical practitioners. Finally, people working in the field need to be constantly aware about the ethical challenges surrounding compulsory admissions.